ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI TEBU RAKYAT DI KECAMATAN BUNGAMAYANG KABUPATEN LAMPUNG UTARA - Thomas Mayang Andriadi; Fembriarti Erry Prasmatiwi; Maya Riantini (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The objectives of this research were to find out the income of sugar cane farming, household income of sugar cane farmers, household welfare level, and factors that affect the welfare level of sugar cane farmer households in Bungamayang Sub-District. The location was determined purposively, considering that Bungamayang Sub-District has been the center of sugar cane production in North Lampung Regency. The number of respondents in this research were 54 farmers taken randomly. Data were collected in April -May 2019.  The analytical method used for the first and second objectives was farm analysis, the third objective used Sajogyo welfare level analysis and the fourth objective used binary logit analysis. The study shows that average income of sugar cane farming is IDR23,161,313.80/hectare.  Average annual household income is IDR44,295,593.33 and the contribution of sugar cane farming income to household income is 57.52 percent.  Based on the criteria of Sajogyo, sugar cane farmer households are included in the sufficient category. Household income positively affects welfare level, while the number of family members negatively affects the welfare level of sugar cane farmers in Bungamayang Sub-District.Key words: farmer households, income, sugar cane, welfare level